AB0869 Subclinical atherosclerosis in greek patients with spondyloarthropathy. (23rd January 2014) - Papagoras, C.; Charisiadi, A.; Margariti, P.; Saougou, I.; Markatseli, T.E.; Kaltsonoudis, E.; Zikou, A.K.; Drosos, A.A.
Abstract : Background: Chronic arthritis, particularly rheumatoid arthritis (RA), has been associated with accelerated atherosclerosis. Ultrasound-assessed carotid intima-media thickness (IMT) has been suggested as a surrogate marker of atherosclerosis and the risk for future cardiovascular events. An increased IMT has been observed in patients with RA, but also ankylosing spondylitis (AS) and psoriatic arthritis (PsA) as compared to non-arthritis controls in various ethnic groups. Objectives: To study subclinical atherosclerosis in Greek patients with spondyloarthritis (SpA). Methods: In a case-control study, non-diabetic patients with AS or PsA followed in a single tertiary Rheumatology center were evaluated for potentially modifiable risk factors for atherosclerosis (obesity, smoking, arterial hypertension, serum lipids and lipoproteins), while they all underwent carotid ultrasonography and measurement of carotid IMT. Age- and sex-matched volunteers without arthritis or diabetes served as controls. Results: Forty-nine patients were examined (22 with AS, 27 with PsA). They were 35 males and 14 females with a mean age (SD) 45.5 (12.4) years. They were compared to 49 age- and gender-matched controls. The patients' mean (SD) carotid IMT was 0.071 (0.018) cm, which was significantly greater than the carotid IMT of the controls [mean (SD) 0.063 (0.016) cm, p=0.017]. Comparing the potentially modifiable cardiovascular risk factors, SpA patients were no more obese than controls in terms of body mass index or waist-to-hip ratio, they had a similar prevalence of hypertension, but they were significantly more often smokers than controls (69.4% vs 26.5%, p=0.02). In terms of lipid profile, SpA patients had significantly lower triglyceride levels than controls (103 mg/dL vs 131.1 mg/dL, p=0.012), but the levels of the rest of the lipid parameters [total cholesterol, high and low density lipoprotein cholesterol, Apolipoprotein AI (ApoAI), ApoB, ApoE, Lipoprotein (α)] were similar between patients and controls. Conclusions: Patients with spondyloarthritis have enhanced atherosclerosis compared to non-SpA controls. Although differential exposure to cigarette smoking is a significant confounding factor, our results are in line with reports from other ethnic groups suggesting that SpA patients have more advanced atherosclerosis compared to age-and sex-matched non-SpA controls. Disclosure of Interest: None Declared